CLINICAL EVALUATION OF GUGGULU TIKTAKA GRITHA MATRAVASTI AND PRAVALAPISTI IN THE MANAGEMENT OF ASTHI KSHAYA W.S.R TO OSTEOPOROSIS - ray, *Vasu; rao, S. Ramalingeswara; Srinivasulu, J (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda explains health as an equilibrium of the Dhatus â€œDhatu Samyamarogataâ€. Among the Dhatus, Asthi is blessed with the function of Shareera Dharana. Any derangement in Asthi results in disease. Being the principle seat of Vata dosha, Asthi related Rogas generally show a Vata dominance in pathology. In Ayurveda both Vridhi and kshaya are mentioned as the pathological states of Dhatus. Osteoporosis can be placed under the spectrum of Asthikshaya. Classics mention the use of Vasti prepared with Tikta Dravya, Ksheera and Ghrita for the treatment of Asthi Kshaya. The present study was undertaken to assess the efficacy of Guggulu Tiktakagritha matravasti and Pravalapisti in the management of Osteoporosis. A total number of 10 patients were selected and treated with Matra vasti for a period of 11days along with Pravalapisti 250mg (oral) B.D. The combined therapy of Vasti and Pravalapisti showed encouraging results in the subjective and objective parameters of Osteoporosis.